Evaluation of OxPL Levels in Patients Undergoing Coronary Angiography: A Cross-Sectional Study - Nikdoust, Farahnaz; Lashkari Zadeh, Farzaneh; Tabatabaei , Seyed Abdolhussein (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Coronary ectasia is one of the prevalent cardiovascular diseases worldwide. It causes many deaths annually ranged between 9% to 10% which is dependent on related risk factors. The main pathogenesis has not been determined yet; however, it has been shown, that increased lipid profiles and their oxidation in patients can cause endothelial cell dysfunction and thrombosis. Therefore, here we investigated the oxidized phospholipids (OxPLs) role in the pathogenesis of coronary artery disease. Methods: This cross-sectional study was performed in Shariati Hospital, Tehran. Accordingly, patients with coronary artery angiography indications (n=360) were included and classified into one of the following three groups, based on the angiographic results: 1) normal coronary artery (not dysfunction in vessels) or mild CAD (only intimal irregularity or less than 3% narrowing without ectasia); 2) vessel dilation more than 1.5 times compared to the normal part of the vessel or compared to the normal size according to age and gender in one or more coronary vessels; and 3) patients with more than 50% stenosis in one of the coronary arteries. The peripheral blood was collected from patients in EDTA anticoagulants container tubes and the OxPL level was measured using an ELISA kit. Results: The results showed that the amount of OxPL in the third and second groups was higher than in the first group. It was also found that hyperlipidemia, diabetes, hypertension, and smoking were higher in the third and second groups; all mentioned findings were statistically significant (p-value <0.05). Conclusion: According to the findings of this study, it was shown that an increase in OxPL in patients with coronary ectasia can be considered as a risk factor for disease progression; OxPL measurement can be used to identify high-risk individuals. *Corresponding Author: Seyed Abdolhussein Tabatabaei; Email: tabatabaeiseyedah@gmailcom; ORCID iD: 0000-0001-5091-6066 Please cite this article as: Nikdoust F, Lashkari Zadeh F, Tabatabaei SA. Evaluation of OxPL Levels in Patients Undergoing Coronary Angiography: A Cross-Sectional Study. Arch Med Lab Sci. 2021;7:1-6 (e12). https://doi.org/10.22037/amls.v7.34602